Diagnostic value of lung ultrasonographic parameters in predicting outcomes of coronavirus disease 2019 (COVID-19) in oxygen-dependent patients requiring intensive care unit treatment - Kalashnyk, K. V.; Kolesnyk, M. Yu.; Riabokon, O. V.; Cherkaskyi, V. V.; Калашник, Кирило Вадимович; Колесник, Михайло Юрійович; Рябоконь, Олена Вячеславівна; Черкаський, Володимир Васильович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim – to determine the diagnostic value of lung ultrasound parameters in predicting outcomes of coronavirus disease 2019 (COVID-19) in oxygen-dependent patients requiring intensive care unit treatment. Materials and methods. We examined 105 patients with COVID-19 who needed supplemental oxygen and were treated in the Department of Anesthesiology and Intensive Care. The age of patients ranged between 39 and 80 years, 63 participants were male and 42 – female. To determine the diagnostic value of lung ultrasound parameters in predicting the severe course of COVID-19 in oxygen-dependent patients, they were divided into groups: Group I – recovered patients (n = 39); Group II – patients with a fatal outcome (n = 66). In all the patients, the diagnosis of COVID-19 was confirmed by RNA-SARS-CoV-2 detection in nasopharyngeal swab specimens. The patients were examined and treated according to the Protocol of the Ministry of Health of Ukraine. The lung ultrasound protocol used in the study included 14 lung examination zones and a score of lung tissue infiltration degree from 0 to 3 points. Statistical processing of the data was performed with Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. In oxygen-dependent patients with severe COVID-19 and a fatal outcome, infiltrative changes in the lung parenchyma were more severe based on the lung ultrasound total score both at the time of admission (p < 0.01) and after 5 days of treatment (p < 0.01). The cutoff score of ≥19 at the time of hospitalization (AUC = 0.753, p < 0.01; sensitivity – 76.9 %, specificity – 68.2 %) and ≥17 after 5 days of treatment (AUC = 0.799, p < 0.01; sensitivity – 71.4 %, specificity – 92.1 %) had a prognostic value for assessing the risk of death in oxygen-dependent patients with severe COVID-19. A lung ultrasound score >19 at the time of admission increased the risk of death by 2.96 times (RR = 2.96, 95 % CI 1.43–2.87, p < 0.001). Lung ultrasound found pleural effusion only in oxygen-dependent COVID-19 patients who died. In the treatment dynamics after 5 days, the rate of pleural effusion detection in this group of patients was three times increased (from 9.1 % to 27.3 %, p < 0.01). Conclusions. The study has revealed the diagnostic value of lung ultrasound parameters in predicting outcomes of COVID-19 in oxygen-dependent patients requiring intensive care unit treatment. Cutoffs of the total score characterizing the degree of lung tissue infiltration have been determined, that allowing to assert a high probability for a lethal outcome of the disease. Мета роботи – з’ясувати діагностичну значущість параметрів ультразвукового дослідження легень у прогнозуванні наслідків коронавірусної хвороби COVID-19 у кисневозалежних хворих, які потребують лікування у відділенні інтенсивної терапії. Матеріали і методи. Обстежили 105 хворих на COVID-19, які потребували кисневої підтримки та перебували на лікуванні у відділенні анестезіології та інтенсивної терапії. У дослідження залучили 63 чоловіків і 42 жінок, вік хворих – від 39 до 80 років. Для з’ясування діагностичної значущості параметрів ультразвукового дослідження (УЗД) легень у прогнозуванні перебігу COVID-19 у кисневозалежних хворих із тяжким перебігом обстежених поділили на групи: I – пацієнти, які одужали (n = 39); II – хворі з летальним наслідком (n = 66). У всіх хворих діагноз COVID-19 підтверджено виділенням із носоглоткового слизу RNA-SARS-CoV-2. Пацієнтів обстежили та лікували згідно з чинним протоколом МОЗ України. Протокол УЗД легень, який застосовано під час роботи, передбачав обстеження 14 зон легень і бальне оцінювання ступеня інфільтрації легеневої тканини (від 0 до 3 балів). Статистично результати опрацювали у програмі Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Результати. У кисневозалежних пацієнтів із тяжким перебігом COVID-19, у яких надалі зафіксували летальний наслідок хвороби, ступінь виразності інфільтративних змін паренхіми легень виявився вищим за сумою балів під час УЗД легень і при госпіталізації (р < 0,01), і через 5 днів лікування (р < 0,01). Прогностичне значення щодо оцінювання ризику летального наслідку у кисневозалежних хворих із тяжким перебігом COVID-19 мав межовий рівень суми балів ≥19 під час госпіталізації (AUC = 0,753, р < 0,01; чутливість – 76,9 %, специфічність – 68,2 %) та ≥17 через 5 діб лікування (AUC = 0,799, р < 0,01; чутливість – 71,4 %, специфічність – 92,1 %). Сума балів >19, встановлена під час УЗД легень при надходженні цих хворих, свідчила про підвищений ризик смерті у 2,96 раза (RR = 2,96, 95 % CI 1,43–2,87, p < 0,001). Наявність випоту у плевральних порожнинах у кисневозалежних хворих на COVID-19, за даними УЗД легень, зафіксували лише у пацієнтів, у яких надалі настав летальний наслідок. У динаміці через 5 діб лікування частота виявлення гідратораксу у цієї групи хворих збільшувалася втричі (з 9,1 % до 27,3 %, p < 0,01).
Діагностична значущість параметрів ультразвукового дослідження легень у прогнозуванні наслідків коронавірусної хвороби COVID-19 у кисневозалежних хворих, які потребують лікування у відділенні інтенсивної терапії
Kalashnyk K. V. - ORCID ID: 0000-0002-4532-8953; Kolesnyk M. Yu. - ORCID ID: 0000-0001-7566-1899; Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803.
Keywords: coronavirus disease; COVID-19; lung; diagnostic ultrasound; lung ultrasound; diagnosis; treatment; prognosis; коронавірусна хвороба; ультразвукове дослідження легень; діагностика; лікування; прогноз